Kinetic analysis of metal uptake by dry and gel alginate particles - Lagoa, Ricardo (2016)
The kinetics of metal uptake by gel and dry calcium alginate beads was analysed using solutions of copper or lead ions. Gel beads sorbed metal ions faster than the dry ones and larger diffusivities of metal ions were calculated for gel beads: approximately 10−4 cm2/min vs. 10−6 cm2/min for dry beads. In accordance, scanning electron microscopy and nitrogen adsorption data revealed a low porosity of dry alginate particles. However, dry beads showed higher sorption capacities and a mechanical stability more suitable for large-scale use. Two sorption models were fitted to the kinetic results: the Lagergren pseudo-first order and the Ho and McKay pseudo-second order equations. The former was found to be the most adequate to model metal uptake by dry alginate beads and kinetic constants in the orders of 10−3 and 10−2 min−1 were obtained for lead solutions with concentrations up to 100 g/m3. The pseudo-first order model was also found to be valid to describe biosorbent operation with a real wastewater indicating that it can be used to design processes of metal sorption with alginate-based materials.